Transboundary Succession of Business: Problems Related to Practice - Kirillova, Elena Anatolyevna; Pozdnyakova, Elena Vladimirovna; Gorevoy, Evgeniy Dmitrievich; Ershova, Inna Vladimirovna; Nadezhin, Nikolay Nikolaevich (International Journal of Economics and Financial Issues, 2015)
The article considers civil aspects of optimizing business succession related to various national public orders for the purpose of defining the most efficient solutions. Some conflicting issues of the substantial law applied to succession were researched taking into account the fact that every state has its own international private law that determines the boundaries of applying foreign law. These issues are extremely important in case of conflicts between national public orders that have their own views on regulating transboundary succession of business. The goal of the research is to find the ways to overcome difficulties that arise when exercising succession rights in case of transboundary succession of enterprises and their branches. Scientific novelty of the research lies in revealing a number of urgent problems on the basis of the comprehensive approach to studying and analyzing business succession complicated by a foreign element taking into account the existing scientific research results. Special methods of the theoretically legal science were used during the research. The principle conclusion made in this article is as follows: in case of transboundary succession of business it must be succeeded as a unit in spite of the differences of legal systems of European countries. Herewith, international conventions that regulate succession legal relationship must contain these recommendations. In addition, in case of owning business in several countries, for the purpose of optimizing succession, it is recommended to apply the procedure of estate planning. Keywords: succession, successor, inheritance, devolution, public order. JEL Classifications: F23; F42; F51; K41